2015
DOI: 10.1021/acs.chemmater.5b00056
|View full text |Cite
|
Sign up to set email alerts
|

Critical Descriptor for the Rational Design of Oxide-Based Catalysts in Rechargeable Li–O2Batteries: Surface Oxygen Density

Abstract: Li−O 2 batteries provide high-capacity energy storage, but for aprotic Li−O 2 batteries, it is reported that the charge−discharge efficiency is ultimately limited by the crystal growth of insoluble Li 2 O 2 on the porous cathode. Catalysts have been reported to improve the nucleation and morphology of Li 2 O 2 , which helps achieve high energy densities. We provide a new insight into the catalytic mechanism of the oxygen reduction reaction (ORR) in aprotic Li−O 2 batteriesthe oxygen sites on the surface play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 52 publications
0
55
0
Order By: Relevance
“…The initial reactions process includes the adsorption, dissociation, and one‐electron reduction of O 2 molecules at cathode/electrolyte interfacenormalO2+normalO2normalO2+normale+Li+LiO2where the dissolved O 2 molecules in solution are absorbed onto the active sites of the cathode surface in the initial stage of discharging (Equation ). After that, the adsorbed O 2 molecules (expressed as O 2 *, and “*” refers to the adsorbed species) are reduced and bonded with solvated Li + cations to form adsorbed LiO 2 by one‐electron reduction reaction (Equation ) …”
Section: The Mechanism Of Aprotic Li–o2 Batterymentioning
confidence: 99%
“…The initial reactions process includes the adsorption, dissociation, and one‐electron reduction of O 2 molecules at cathode/electrolyte interfacenormalO2+normalO2normalO2+normale+Li+LiO2where the dissolved O 2 molecules in solution are absorbed onto the active sites of the cathode surface in the initial stage of discharging (Equation ). After that, the adsorbed O 2 molecules (expressed as O 2 *, and “*” refers to the adsorbed species) are reduced and bonded with solvated Li + cations to form adsorbed LiO 2 by one‐electron reduction reaction (Equation ) …”
Section: The Mechanism Of Aprotic Li–o2 Batterymentioning
confidence: 99%
“…[78] The morphology of the final discharge products can be also tuned by the current density. In metal-oxide catalysts, surface oxygen sites can act as anchoring or growth sites for the discharge product, [82,83] through chemical bonding between surface oxygen sites and Li ions (Figure 9). [78,79] The influence of cell operation temperature has been also studied by Tan et al, who showed that the higher the operation temperature, the larger the particle size of Li 2 O 2 .…”
Section: Liomentioning
confidence: 99%
“…[78,79] The influence of cell operation temperature has been also studied by Tan et al, who showed that the higher the operation temperature, the larger the particle size of Li 2 O 2 . [82] To validate this prediction, [002] and oriented α-MnO 2 nanowires (NWs) were also studied, to investigate the morphological differences of the discharge products after the initial discharge. [80] Because the cathode catalyst can modulate the nucleation and growth of Li 2 O 2 , it can somehow affect the electrochemical performance of Li-O 2 cells.…”
Section: Liomentioning
confidence: 99%
See 1 more Smart Citation
“…However, many challenges, including poor rate capability, high charge overpotentials, and limited cyclic stability, should be addressed before any real‐world application of LOBs . The sluggish oxygen evolution, the poor contact with the electrode/electrolyte, and the insulating nature of the discharge product are the intrinsic limit for the aforementioned drawbacks of LOBs . They not only limit the depth of the oxygen reduction reaction (ORR) but also raise the barriers for oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%